The Beginning And End Of The Life Cycle - Butler-Sloss GBE, Dame Elizabeth (Journal of Malaysian and Comparative Law, 2019)
Public Lecture delivered at the Faculty of Law of the University of Malaya, Kuala Lumpur, Malaysia, 21 November 2005 by Dame Elizabeth Butler-Sloss GBE, the Chancellor at the University of the West of England, Bristol, The United Kingdom; formerly President of the Family Division of the High Court of Justice.